Pembuatan Model Digital Dan Perencanaan Tahapan Pekerjaan Struktur Atas Gedung Presisi 3 Mabes Polri Jakarta Selatan Berbasis Building Information Modelling - Faturahman, Rifat Azma; Maulana Fadhilah, Faris; Wusqo, Urwatul; Widyaningsih, Yulia (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
Technological advancements in the construction sector are growing massively, making digitalization a necessity. Through digitization, the process of planning, implementing, and managing projects can be done more efficiently and accurately, considering that all information related to the project is centralized in one integrated base. Building Information Modeling (BIM) is a digital system for building modeling that contains information about all aspects of a well-managed building. The object of this study will review the Precision 3 MABES POLRI South Jakarta Building by applying Building Information Modelling (BIM) based digitization. At MABES POLRI Precision 3 building project, the application of BIM has not been fully carried out, so it still uses conventional methods. In accordance with the Regulation of the Minister of PUPR No. 22/PRT/M/2018, the use of Building Information Modeling (BIM) must be applied to non-simple buildings with the criteria of building area above 2,000 m2 above 2 floors. The building, which began construction in February 2024, has a building area of 11,200 m2 consisting of 10 floors + 1 roof, which can be categorized as a non-simple building. Therefore, in this final project, the author intends to apply BIM for the method by modeling the concept of 4D and 5D applications of dimensional BIM which includes a 3D top structure model to get the right Quantity Take Off output and planning of implementation stages as a result of this research accompanied by detailed top structural elements, and planning the stages of implementing the top structure of the MABES POLRI Precision 3 Building project using Tekla Structures 2024 - Student Version software.